A Hybrid Fuzzy Approach to Success in E-Commerce Adoption in Iranian Manufacturing SMEs - Amir Hakaki,; Mohsen Shafiei Nikabadi, (Asian Academy of Management Journal, 2022)
E-commerce adoption is one of the most controversial subjects among small and medium enterprises (SME)s in Iran. The present study is conducted with the aim of identifying the most important factors in e-commerce adoption – reviewing the causal relationships and clustering them. To identify the most important factors, the data is collected by questionnaires filled by 95 experts who were chosen as researchers’ judgment. Examining the causal relationships among the studied factors and clustering is done by fuzzy decision making trial and evaluation laboratory (DEMATEL) and interpretive structural modelling (ISM) techniques respectively. Data is collected from 12 experts and analysed by MATLAB and EXCEL software. According to the results, government support as one of the causal factors among critical factors effecting on e-commerce adoption is the highest influential factor, along with cost of public’s training. Both factors are put into the first cluster. Moreover, organisational flexibility plays an intermediate role between the first and the third cluster.